Meningkatkan Keaktifan dan Hasil Belajar Melalui Penerapan Model Pembelajaran Wide Game pada Peserta Didik Kelas VIID SMP Negeri 13 Tegal - Suharni Suharni (Universitas Pendidikan Mandalika, 2021)
The purpose of this study is to increase the activeness and learning outcomes of students through the Wide Game learning model in economic activity material. This research method using descriptive method. The subjects in this study were 31 students of class VIID SMP Negeri 13 Tegal. The research instrument used a questionnaire and data analysis techniques using descriptive analysis. The results of this study indicate that there is an increase in the activeness and learning outcomes of students through the Wide Game learning model in economic activity material. This is evidenced by the data in the first cycle with an average value of 70.97 and those who completed 58.04% increased the average value of 81.23 and those who completed were 87.10% in the second cycle. This increase is also accompanied by changes in behavior, students are more active, and respect others in doing tasks.